2020
DOI: 10.5507/bp.2019.016
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cholesteryl ester transfer protein (CETP) gene variants with pituitary adenoma

Abstract: Aim. The aim was to evaluate the association of CETP (rs5882 and rs708272) single nucleotide polymorphisms with the presence, invasiveness, hormonal activity and recurrence of pituitary adenoma (PA). Methods. The study group included 142 patients with PA and the control group, 753 healthy subjects. The genotyping of CETP (rs5882 and rs708272) was performed using a real-time PCR method. Results. After statistical analysis we found that CETP rs708272 genotype G/A under the over-dominant model was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…CETP is highly expressed in many cancers, such as colorectal, gastric, breast, pituitary adenoma and gallbladder cancers. 8,[22][23][24][25] Recent studies on the significance of CETP in breast cancer development have confirmed that CETP can help improve the survival outcomes of breast cancer cells as well as promote resistance to apoptosis. Furthermore, Mihajlovic et al indicated that CETP activity increased during tumor progression in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…CETP is highly expressed in many cancers, such as colorectal, gastric, breast, pituitary adenoma and gallbladder cancers. 8,[22][23][24][25] Recent studies on the significance of CETP in breast cancer development have confirmed that CETP can help improve the survival outcomes of breast cancer cells as well as promote resistance to apoptosis. Furthermore, Mihajlovic et al indicated that CETP activity increased during tumor progression in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the histopathological view group was divided into invasive and non-invasive; based on hormone levels in blood serum, two groups were created: active and inactive PA. Relapse was diagnosed if the enlargement of a residual tumor or a new growth was noticed and documented on follow-up MRI. PA’s hormonal activity, recurrence [ 18 ] and invasiveness [ 19 ] were previously briefly described.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our inclusion and exclusion criteria (27), two groups were formed in our study: PA group (n=141) and controls (n=287) ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction and genotyping. The evaluation of PA hormonal activity, invasiveness and recurrence has been described in detail previously (27). DNA extraction and genotyping were based on a real-time polymerase chain reaction (RT-PCR) method (28).…”
Section: Evaluation Of Pas' Hormonal Activity Invasiveness Recurrenmentioning
confidence: 99%